What we talk about when we talk about epistemic justification. Issue 7 (16th November 2016) - Lyons, Jack C.
Abstract: Stewart Cohen argues that much contemporary epistemological theorizing is hampered by the fact that 'epistemic justification' is a term of art (rather than something we all pretheoretically understand) and one that is never given any serious explication in a non-tendentious, theory-neutral way. He suggests that epistemologists are therefore better off theorizing in terms of rationality, rather than in terms of 'epistemic justification'. Against this, I argue that even if the term 'epistemic justification' is not broadly known, the concept it picks out is quite familiar, and partly because it's a term of art, justification talk is a better vehicle for philosophical theorizing. 'Rational' is too unclear for our philosophical purposes, and the fact that 'epistemic justification' gets fleshed out by appeal to substantive, controversial theses is no obstacle to its playing the needed role in epistemological theorizing.